Numismatic evidence (or not) for the aphippodroma horse race at Larisa - Mack, Rosanagh (KOINON: The International Journal of Classical Numismatic Studies, 2019)
The horse featured prominently on the coinage of the Thessalian city of Larisa, a reflection of its role in daily life, legend, and as an economic product. Among an issue of drachmas with the profile head of the nymph Larisa on the obverse, is a particularly unusual reverse type which depicts a horseman standing behind, and restraining a horse. This issue was short-lived, dated to c. 404 BC, and the type reappears again c. 370s-360s, with the facing head of Larisa on the obverse. This reverse type has generally been seen as a horseman about to mount, but it is also often cited as evidence for the race known as the aphippodroma, during which the horseman is presumed to have dismounted and remounted his galloping horse. Gallis sees this type as the representation of this race, commenting that ‘its importance as a Thessalian tradition and also as an event with great appeal to the public can be seen in the fact that it was represented on Larisaean coins of the fourth century BC.’ In his definition of the aphippodroma, Golden explains that this was the ‘dismounting horse race’ in which the rider dismounted and mounted in the course of the race, and that it is depicted on the coins of Larisa in Thessaly.